Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1302/0301-620x.99b1.38054
|View full text |Cite
|
Sign up to set email alerts
|

Ankle joint pressure changes in high tibial and distal femoral osteotomies

Abstract: The re-alignment of coronal plane knee deformities by HTO and DFO altered ankle pressure characteristics. When the subtalar joint was fixed in the varus position, migration of centre of force after HTO was more significant than when the subtalar joint was fixed in valgus. Cite this article: Bone Joint J 2017;99-B:59-65.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Therefore, the hindfoot flexibility can influence the calcaneus position after the correction of genu varum deformity. A previous cadaveric study also showed that the lateral migration of ankle joint pressure was more significant when the subtalar joint was fixed in the varus position [10]. Second, total knee arthroplasty and HTO can change the rotational alignment of the lower extremities [20,21].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Therefore, the hindfoot flexibility can influence the calcaneus position after the correction of genu varum deformity. A previous cadaveric study also showed that the lateral migration of ankle joint pressure was more significant when the subtalar joint was fixed in the varus position [10]. Second, total knee arthroplasty and HTO can change the rotational alignment of the lower extremities [20,21].…”
Section: Discussionmentioning
confidence: 92%
“…Conversely, few studies evaluated the WBL ratio of the ankle joint after knee arthroplasty or HTO, although it is an HKA, hip-knee-ankle; WBL, weight-bearing line; AJLO-G, ankle joint line orientation relative to the ground important factor that affects the joint biomechanics and load distribution [10,11]. This was due to the lack of radiologic techniques to measure the WBL ratio of the ankle joints.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a cadaveric study by Suero et al, 10 moderate to large changes in proximal tibial alignment by medial open‐wedge HTO resulted in a significantly decreased tibiotalar contact surface area and changes in intraarticular ankle pressures. Another cadaveric study also assessed the effect of HTO and distal femoral osteotomies on the pressure characteristics of the ankle joint 11 . They examined the effect on various conditions including two different (5 and 10) degrees of realigning osteotomy, and whether the subtalar joint was either mobile or fixed.…”
Section: Introductionmentioning
confidence: 99%